Bacterial processing of glucose modulates C. elegans lifespan and healthspan - Samuel F. Kingsley (Nature Portfolio, 2021)
Abstract Intestinal microbiota play an essential role in the health of a host organism. Here, we define how commensal Escherichia coli (E. coli) alters its host after long term exposure to glucose using a Caenorhabditis elegans-E. coli system where only the bacteria have direct contact with glucose. Our data reveal that bacterial processing of glucose results in reduced lifespan and healthspan including reduced locomotion, oxidative stress resistance, and heat stress resistance in C. elegans. With chronic exposure to glucose, E. coli exhibits growth defects and increased advanced glycation end products. These negative effects are abrogated when the E. coli is not able to process the additional glucose and by the addition of the anti-glycation compound carnosine. Physiological changes of the host C. elegans are accompanied by dysregulation of detoxifying genes including glyoxalase, glutathione-S-transferase, and superoxide dismutase. Loss of the glutathione-S-transferase, gst-4 shortens C. elegans lifespan and blunts the animal's response to a glucose fed bacterial diet. Taken together, we reveal that added dietary sugar may alter intestinal microbial E. coli to decrease lifespan and healthspan of the host and define a critical role of detoxification genes in maintaining health during a chronic high-sugar diet.